Biocompatible carbon quantum dots for intelligent sensing in food safety applications: Opportunities and sustainability. (March 2023) - Khan, A.; Ezati, P.; Kim, J.-T.; Rhim, J.-W.
Abstract: Carbon quantum dots (CQDs) are widely used in various industries due to their non-toxic, biocompatibility, antibacterial, and tunable photoluminescence properties. In particular, interest in developing smart/intelligent sensing systems using CQDs is increasing in the food industry. The integration of CQDs-sensing platforms with food packaging could provide a means to allow real-time monitoring of the quality change of packaged foods. A novel fluorescent carbon nanomaterial, CQD, is considered a promising candidate for developing novel intelligent nanosensors for food quality control. Therefore, it is noteworthy to analyze new information on the proficiency of CQD-based sensing systems in developing sustainable, innovative packaging materials. Although CQDs have been used for several potential applications, the focus of the current review is to summarize recent research and developments on CQD-based sensors that can be used in the food industry. This review also outlines the potential challenges and prospects of modern CQDs and real-time intelligent sensing of food quality changes.